Selected Factors Related to the Risk of Falls among Hospitalized Older Adult Patients - wongpiriyayothar, Apinya; Ruangchaithaweesuk, Kunnicha; Pulperm, Palita; Ninnun, Wichuta (Jurnal Keperawatan Soedirman, 2025)
Hospitalized older adult patients have a high risk of falls due to their health conditions. Therefore, this study aims to examine the relationships between body mass index (BMI), osteoarthritis, cognitive function, activities of daily living (ADLs), and the risk of falls among hospitalized older adult patients. The researchers employed a descriptive correlational research design with 110 older adult patients admitted to a university hospital in Northeast Thailand. The patients were selected through simple random sampling by the Osteoarthritis Screening Form, the Cognitive Impairment Test, the Barthel Index Scale, and the Morse Fall Scale. The data were analyzed using descriptive statistics and Spearman's rank correlation. The study's results demonstrated that three factors had statistically significant correlations with the risk of falls: osteoarthritis (rs = 0.31, p = 0.001), cognitive function (rs = 0.26, p = 0.008), and ADLs (rs = -0.45, p = 0.001). Meanwhile, BMI was not correlated with the risk of falls. This study concludes that osteoarthritis, cognitive function, and ADLs are associated with an increased risk of falls. Therefore, nurses should evaluate patients’ risk of falls, related factors, create interventions to promote exercise, and enhance ADL skills to reduce the risk of falls in hospitalized older adult patients.